Data analytics: effective methods for presenting results - Samaddar, Subhashish; Nargundkar, Satish (London CRC Press, 2019)
"Effective presentation of analytical results is the key to close a project successfully. With the meteoric rise in the popularity of data science and analytics, business executives focus on analytics' strategic interpretation and managerial implications, as well as value creation from analytics. One of the major challenges faced by analytics specialists is to be able to present and communicate the results of their analyses in business terms. With this book, readers learn the strategies of effectively communicating and presenting quantitative analytical results to their clients and senior management"--
Know your audience -- Presenting results from commonly used modeling techniques -- Visualization to improve analytics -- Marketing models - Demonstrating effectiveness to clients -- Restaurant management : Convincing management to change -- Project presentations in the armed forces -- Inventory management - Customizing presentations for management layers -- Executive communication in process improvement -- Internal auditing - Seeking action from top management to mitigate risk -- Consumer lending : Winning presentations to investors -- As you can see.
Includes Index.
Keywords: Business; Business requirements analysis; Business analysts